2017
DOI: 10.3390/s17020363
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Graphene-Based Sensors and Application on Detecting SF6 Decomposing Products: A Review

Abstract: Graphene-based materials have aroused enormous focus on a wide range of engineering fields because of their unique structure. One of the most promising applications is gas adsorption and sensing. In electrical engineering, graphene-based sensors are also employed as detecting devices to estimate the operation status of gas insulated switchgear (GIS). This paper reviews the main synthesis methods of graphene, gas adsorption, and sensing mechanism of its based sensors, as well as their applications in detecting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 63 publications
0
17
0
Order By: Relevance
“…Detailed analysis about CNT and graphene‐based gas sensors in this field can be found in [92, 93]. It is worth noting that C‐based sensing materials usually have good sensing lifespan for gas sensing due to their strong surface reactivity, and the recycling sensing performance could up to 20–25 days [92, 93].…”
Section: Application Of Nanomaterials‐based Gas Sensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed analysis about CNT and graphene‐based gas sensors in this field can be found in [92, 93]. It is worth noting that C‐based sensing materials usually have good sensing lifespan for gas sensing due to their strong surface reactivity, and the recycling sensing performance could up to 20–25 days [92, 93].…”
Section: Application Of Nanomaterials‐based Gas Sensorsmentioning
confidence: 99%
“…For example, Co‐doped CNT possesses better adsorption behaviour upon SOF 2 and SO 2 F 2 than those of SO 2 and H 2 S; Pd‐ and Ni‐doped CNTs are good candidates for SO 2 sensing; Ag‐doped graphene is a desirable sensor for SO 2 F 2 detection; and Rh‐doped CNT could be applied as gas adsorbent for impurity gases removal in SF 6 insulation devices due to its non‐preference and strong chemisorption towards four typical species. Detailed analysis about CNT and graphene‐based gas sensors in this field can be found in [92, 93]. It is worth noting that C‐based sensing materials usually have good sensing lifespan for gas sensing due to their strong surface reactivity, and the recycling sensing performance could up to 20–25 days [92, 93].…”
Section: Application Of Nanomaterials‐based Gas Sensorsmentioning
confidence: 99%
“…Tian et al proposed that AB‐stacked bilayer graphene transistors have high output current density, and their intrinsic voltage gain is up to 77, which is many times higher than that of single‐layer graphene . In addition, it can be used to improve the on–off ratio of the spin valve in pseudo‐spin simulation and the response rate of the bolometer …”
Section: Introductionmentioning
confidence: 99%
“…[20] In addition, it can be used to improve the on-off ratio of the spin valve in pseudospin simulation [21,22] and the response rate of the bolometer. [23][24][25][26]…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has indicated that these characteristic gases can accelerate the corrosion rate of facilities and increase the probability of system paralysis Zhou et al, 2018b). Therefore, it is of great necessity to evaluate the operational status of GIS equipment by effectively detecting these typically decomposed products of SF 6 (Zhang X. X. et al, 2017b;Zhou et al, 2018d). In this respect, bidimensional nanomaterials have captured widespread attention for its multiple physical and chemical properties in the detection of SF 6 decomposed gas (Zhou et al, 2018a;Chen et al, 2018).…”
Section: Introductionmentioning
confidence: 99%